CD59 polymorphisms are associated with gene expression and different sexual susceptibility to pemphigus foliaceus - Amanda Salviano-Silva; Maria Luiza Petzl-Erler; Angelica Beate Winter Boldt (Taylor & Francis Group, 2017)
Pemphigus foliaceus (PF) is an autoimmune disease, endemic in Brazilian rural areas, characterized by acantholysis and accompanied by complement activation, with generalized or localized distribution of painful epidermal blisters. CD59 is an essential complement regulator, inhibiting formation of the membrane attack complex, and mediating signal transduction and activation of T lymphocytes. CD59 has different transcripts by alternative splicing, of which only two are widely expressed, suggesting the presence of regulatory sites in their noncoding regions. To date, there is no association study with polymorphisms in CD59 noncoding regions and susceptibility to autoimmune diseases. In this study, we aimed to evaluate if CD59 polymorphisms have a possible regulatory effect on gene expression and susceptibility to PF. Six noncoding polymorphisms were haplotyped in 157 patients and 215 controls by sequence-specific PCR, and CD59 mRNA levels were measured in 82 subjects, by qPCR. The rs861256-allele-G (rs861256*G) was associated with increased mRNA expression (p = .0113) and PF susceptibility in women (OR = 4.11, p = .0001), which were also more prone to develop generalized lesions (OR = 4.3, p = .009) and to resist disease remission (OR = 3.69, p = .045). Associations were also observed for rs831625*G (OR = 3.1, p = .007) and rs704697*A (OR = 3.4, p = .006) in Euro-Brazilian women, and for rs704701*C (OR = 2.33, p = .037) in Afro-Brazilians. These alleles constitute the GGCCAA haplotype, which also increases PF susceptibility (OR = 4.9, p = .045) and marks higher mRNA expression (p = .0025). In conclusion, higher CD59 transcriptional levels may be related with PF susceptibility (especially in women), probably due to the effect of genetic polymorphism and to the CD59 role in T cell signal transduction.